(untitled) (JURNAL GEOCELEBES, 2023)
Groundwater as a source of clean water which is very important in fulfilling the needs of humans is considered suitable as the main alternative. Layers investigation of soil that is permeable to water (aquifer) in Mattoangin Village, Bantimurung District, Maros Regency aims to obtain 2D model map of the distribution of groundwater below the surface. The presence of groundwater stored in aquifers can be explored by geophysical methods. The Wenner-Schlumberger array has a good resolution so it is deemed suitable for aquifers. The measurement data was processed using Res2DInv software. The exploration resulted in a 2D cross-sectional model of the subsurface resistivity. Based on the results of measurements and data processing, the groundwater aquifer which has the potential to have resistivity values of 9.73-32.7 Ωm on track 1, resistivity values of 6.24-32 Ωm is on track 2 with a depth of 6 - 10 m and resistivity values of 5.68-33, 6 Ωm on track 3 with a depth of 6 - 8 Ωm.